1995
DOI: 10.1086/175593
|View full text |Cite
|
Sign up to set email alerts
|

An extended galactic population of low-luminosity x-ray sources (CVs?) and the diffuse x-ray background

Abstract: The incompatibility of the properties of the x-ray background (XRB) with AGNs contributing > 60% at energies of a few KeV has often been interpreted as being due to a substantial contribution of a new population of yet unrecognized x-ray sources. The existence of such population has been recently suggested also by an analysis of very deep ROSAT observations (Hasinger et al. 1993) which revealed a considerable excess of faint x-ray sources over that expected from QSO evolution models, and that the average spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For some of them only the existence of high excitation [Ne V] emission lines and/or the high X-ray luminosity (Lx > 10 43 erg s" 1 ) in the 0.5-2.0 keV energy band reveal the AGN nature of these objects. Prom the nearly complete (95 %) identification of our ROSAT Deep Surveys we find no indication for new classes of NLXG or of galactic CVs (Maoz & Grindlay 1995), which have been claimed to dominate the soft X-ray counts at fainter fluxes (cf. Paper III).…”
Section: Identification Of the Rosat Deep/ultradeep Surveysmentioning
confidence: 65%
“…For some of them only the existence of high excitation [Ne V] emission lines and/or the high X-ray luminosity (Lx > 10 43 erg s" 1 ) in the 0.5-2.0 keV energy band reveal the AGN nature of these objects. Prom the nearly complete (95 %) identification of our ROSAT Deep Surveys we find no indication for new classes of NLXG or of galactic CVs (Maoz & Grindlay 1995), which have been claimed to dominate the soft X-ray counts at fainter fluxes (cf. Paper III).…”
Section: Identification Of the Rosat Deep/ultradeep Surveysmentioning
confidence: 65%
“…Because of the intrinsic difficulties in detecting single objects and of the expected relative abundance of ONSs in the Galaxy, it is natural to consider their overall emission and more specifically their contribution to the soft X-ray background, as already suggested by Ostiker, Rees, & Silk (1970). Assuming B ∼ 10 9 G and N ON S ∼ 10 9 , (Zane et al 1995) have recently shown that ONSs accreting the interstellar gas can account for a non-negligible fraction of the observed excess in the soft X-ray background which is not extragalactic in origin but could be produced by a Galactic population (Maoz & Grindlay 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study (Maoz and Grindlay 1995) we have found that a number of previously recognized anomalies in the diffuse x-ray background at soft energies (~0.5-2 keV) can be understood if about 20-30% of the diffuse flux arises from a population of low luminosity sources in a thick disk or flattened halo distribution in the Galaxy. Here we summarize our results and review the arguements that these objects are not accreting neutron stars or black holes but rather white dwarfs (i.e.…”
mentioning
confidence: 98%